Novel anti-myeloma immunotherapies targeting the SLAM family of receptors. (4th May 2017) - Radhakrishnan, Sabarinath Venniyil; Bhardwaj, Neelam; Luetkens, Tim; Atanackovic, Djordje
ABSTRACT: Treatment for multiple myeloma (MM) has significantly advanced in the last decade with the introduction of proteasome inhibitors and immunomodulatory therapies. Unfortunately, MM continues to cause significant morbidity and most patients eventually succumb to the disease. As in other areas of cancer, immunotherapy in MM has also evolved and holds promise to deliver long-lasting remissions or even cure. The signaling lymphocyte activation molecules (SLAM) family of surface proteins represents a group of potential targets for immunotherapy in MM as some of the family members are expressed consistently on plasma cells and also on myeloma propagating pre-plasma cells. Here, we review the SLAM family members in detail, describe their tissue distribution, biologic pathways, as well as relevant pre-clinical studies and clinical trials in MM. Our review demonstrates the value of SLAM family receptors as potential targets for anti-myeloma immunotherapies and outlines how immunotherapeutic approaches can be developed.